ANALYSIS OF USING OF REMOTE SENSING SATELLITE - Козлова, Т. В.; Вольвах, В. С.; Собчук, М. В. (Science-based technologies, 2016)
This article deals with the analysis of manufacturing and launching the spacecraft to the orbit and their usage. The special attention is given to remote sensing satellites and data received from them. The development of remote sensing techniques has been leading to the improvement of opportunities in global environmental monitoring. The article analyses the economic provision and the share of expenses on manufacturing of remote sensing satellites in the general budget of leading spacecraft agencies. The main consumers of remote sensing data are found. The significant application of methods and technologies of remote sensing is involved by national space programs of Ukraine. Disadvantage of its development is insufficient commercialization and the budget provision can be considered as limiting factor. According to profound analysis of dynamics in world space market including remote sensing, the space manufacturing Ukrainian sphere needs increasing the share of world production. The creation of unique space technologies and their establishment on the world space market have to be the basis for competitive advantage and enhancement of the country's competitiveness index.